Big data analytic on block chain across healthcare sector - Shilpa, Miss.; Rahul Sharma, Er; Sartaj Singh, Mr (International Journal of Engineering and Technology, 2018)
Block chain is a decentralized transactional methodology for authorization and updates, in the Cryptocurrencies ecosystem. It is an exploring way in the Cryptocurrencies ecosystem to bit traditional corporate such as the mainstream healthcare and finance. The responsive nature of healthcare data along the lasting provocation of inter-synchronization, healthcare info exchange and patient record matching has created opportunities for a Block chain to maintain the victory of the challenge. The proposed paper aims to put Block chain technology or network based peer to peer authenticate layer on medical big data, for either information portability or set permission during third party involvement during some relevant big data analytic or findings. Based upon propose approaches, healthcare big data can be derived among multiple healthcare service providers, patients and analytic platforms with secure node to node distribution without any centralized ledger or storage point. Â Â